Necessity creates opportunities for chimpanzee tool use. (8th May 2019) - Grund, Charlotte; Neumann, Christof; Zuberbühler, Klaus; Gruber, Thibaud
Abstract : Food scarcity and long distance between food patches foster exploration of ecological opportunities in wild chimpanzees, setting the stage for foraging innovations. Using a combination of field experiments and behavioural observations, we show that chimpanzees engage more with an experimental device containing honey when they have travelled more and fed less immediately before the experiment. Necessity thus tunes the attention and interest of chimpanzees toward potential ecological opportunities, a necessary condition for tool use. Abstract: Although social transmission mechanisms of animal cultures are well studied, little is known about the origins of behavioral innovations, even in established tool users such as chimpanzees. Previous work has suggested that wild chimpanzees are especially prone to engaging with tools during extended periods of low food availability and after long travel, supporting the hypothesis that cultural innovation is facilitated by necessity revealing opportunities. Here, we tested this hypothesis with a field experiment that directly compared subjects' immediate variation in measures of current energy balance with their interest in a novel foraging problem, liquid honey enclosed in an apparatus accessible by tool use. We found that the previous distance traveled directly predicted subjects' manipulations of both the apparatus and the tool, whereas previous feeding time was negatively correlated to manipulation time. We conclude that "necessity" augments chimpanzees' likelihood of engaging with ecological "opportunities, " suggesting that both factors are scaffolding foraging innovation in this and potentially other species.